Tip of the spear: black radicalism, prison repression, and the long attica revolt - Burton, Orisanmi (University of California Press, 2023)
"Tip of the Spear boldly and compellingly argues that prisons are a domain of hidden warfare within US borders. Orisanmi Burton explores what he terms the Long Attica Revolt, a criminalized tradition of Black radicalism that propelled rebellions in New York prisons during the 1970s. The reaction to this revolt illuminates what Burton calls prison pacification: the coordinated tactics of violence, isolation, sexual terror, propaganda, reform, and white supremacist science and technology that state actors use to eliminate Black resistance within and beyond prison walls. Burton goes beyond the state records that other histories have relied on for the story of Attica and expands that archive, drawing on oral history and applying Black radical theory in ways that center the intellectual and political goals of the incarcerated people who led the struggle. Packed with little-known insights from the prison movement, the Black Panther Party, and the Black Liberation Army, Tip of the Spear promises to transform our understanding of prisons-not only as sites of race war and class war, of counterinsurgency and genocide, but also as sources of defiant Black life, revolutionary consciousness, and abolitionist possibility"--